2021
DOI: 10.3390/cancers13112749
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Prediagnostic Circulating Bilirubin Levels and Risk of Gastrointestinal Cancers in the UK Biobank

Abstract: We investigated associations between serum levels of bilirubin, an endogenous antioxidant, and gastrointestinal cancer risk. In the UK Biobank, prediagnostic serum levels of total bilirubin were measured in blood samples collected from 440,948 participants. In multivariable-adjusted Cox proportional hazard regression, we estimated hazard ratios (HR) and 95% confidence intervals (CI) for associations between bilirubin levels and gastrointestinal cancer risk (colorectum, esophagus, stomach, mouth, pancreas, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Studies have reported inconsistent results regarding the relationship between circulating bilirubin levels and risk of CRC. In a Mendelian randomization study (67878 cases), TBIL levels were not associated with the risk of CRC[ 11 ], which was similar to the findings of a meta-analysis and a prospective survey[ 12 , 13 ]. In an approximately 10-year follow-up study by He et al [ 14 ], baseline TBIL levels were found to be negatively correlated with the risk of CRC.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have reported inconsistent results regarding the relationship between circulating bilirubin levels and risk of CRC. In a Mendelian randomization study (67878 cases), TBIL levels were not associated with the risk of CRC[ 11 ], which was similar to the findings of a meta-analysis and a prospective survey[ 12 , 13 ]. In an approximately 10-year follow-up study by He et al [ 14 ], baseline TBIL levels were found to be negatively correlated with the risk of CRC.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, both PC1 and PC3, except for PC3 among women, were inversely associated with total bilirubin, indicating a less favorable metabolic health ( 31 ). Total bilirubin itself could potentially also play a causal role in CRC development, whereby higher circulating levels tended to be inversely associated with CRC risk in UK Biobank ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested that serum bilirubin is associated with the occurrence and development of tumors [ 30 , 31 , 32 , 33 , 34 ]. To the best of our knowledge, this is the first study on the relationship between pretreatment STB and the prognosis of patients newly diagnosed with PCNSL who received HD-MTX-based combination immunochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Cao et al found that pretreatment STB and direct bilirubin were independent prognostic factors in patients with CRC [ 33 ]. In a large-scale prospective study based on data from the UK Biobank, higher levels of pre-diagnostic circulating total bilirubin were significantly inversely associated with the risk of esophageal adenocarcinoma [ 34 ]. In a two-sample Mendelian randomization study, researchers found an inverse association between genetically raised bilirubin levels and the risk of squamous cell lung cancer and HL [ 35 ].…”
Section: Discussionmentioning
confidence: 99%